Welfare reform and public justification. (2nd November 2019) - Eriksen, Andreas; Molander, Anders
ABSTRACT: This paper investigates the conditions of political argument with regard to welfare legislation. It connects to the discussion on the role of ideas in political change but develops a new approach by investigating arguments in light of theories of public justification in a democratic society. The paper uses a recent Norwegian law as the case for studying how politicians frame their arguments for "mandatory activation, " meaning the policy that requires recipients to participate in work-oriented activities. The paper finds that Norwegian advocates of activation use a "justificatory narrative" that presents the new law as a form of paternalistic concern for the benefit recipients. It is argued that this justification can be understood as shaped by certain basic conditions of political viability.